2022
DOI: 10.1186/s12864-022-08501-z
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood transcriptome profiling identifies candidate genes associated with alopecia in male giant pandas (Ailuropoda melanoleuca)

Abstract: Background The giant panda (Ailuropoda melanoleuca) is a threatened species endemic to China. Alopecia, characterized by thinning and broken hair, mostly occurs in breeding males. Alopecia significantly affects the health and public image of the giant panda and the cause of alopecia is unclear. Results Here, we researched gene expression profiles of four alopecia giant pandas and seven healthy giant pandas. All pandas were approximately ten years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 98 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…Because the giant panda genome had already been reported (Li et al, 2010), previous studies of the giant panda transcriptome have mainly focused on mRNA levels from tissues or whole blood (Li et al, 2020;Shen et al, 2022;Zheng et al, 2022). However, how the genes changed in PBMCs of giant pandas after LPS stimulation and what are the similarities and differences of transcriptional profile compared with other mammals are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Because the giant panda genome had already been reported (Li et al, 2010), previous studies of the giant panda transcriptome have mainly focused on mRNA levels from tissues or whole blood (Li et al, 2020;Shen et al, 2022;Zheng et al, 2022). However, how the genes changed in PBMCs of giant pandas after LPS stimulation and what are the similarities and differences of transcriptional profile compared with other mammals are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, fresh tissues of rare and protected species such as the YFP are extremely difficult to obtain, and scholars often use blood tissues collected without causing damage instead of the other tissues for transcriptome studies. Shen et al (2019) explored the cause of baldness in pandas through studying the blood transcriptome and found that the hair-promoting factor Wnt10b was significantly down-regulated and expressed in the blood of pandas with baldness [13]. Liu (2017) performed the comparative analysis of the blood transcriptome of high-altitude and lowaltitude wolves and found that the differentially expressed genes in the blood of the two wolves were significantly enriched in the hypoxia response, aerobic respiration, and ATP metabolism pathways, so as to adapt to the environment at different altitudes [14].…”
Section: Introductionmentioning
confidence: 99%